How do pre-service teacher education students respond to assessment feedback?. Issue 7 (2nd October 2020) - Grainger, Peter
Abstract : Giving effective feedback is an elusive process that continues to receive conflicting reactions from both students and assessors. Despite the feedback loop being acknowledged as essential to effective learning, there is no single process that has been identified as positively impacting on student achievement. Additionally, there is a lack of research in the context of pre-service teacher education in regards to how students are inducted into the process of giving feedback, which can be regarded as 'core business' for any teacher. This article reports on the results of an exploratory study, based on an 'intervention', to determine pre-service teacher student responses to new feedback processes in an initial teacher education course. The results indicated that responses to feedback varied considerably, ranging from those students who preferred more regular feedback mechanisms (such as criteria sheets and annotations on student scripts), to those who preferred a different approach that de-emphasised the role of assessor feedback, and encouraged critical self-reflection and ownership of the learning process in order to promote the development of tacit assessment knowledge. The conclusions are that there is no one feedback mechanism that works best for all students, and that feedback processes are most effective when customised to individual students.